Socioeconomic and programmatic determinants of renewal of membership in a voluntary micro health insurance scheme: evidence from Chakaria, Bangladesh - Mohammad Iqbal; Asiful Haidar Chowdhury; Shehrin Shaila Mahmood; Mohammad Nahid Mia; S. M. A. Hanifi; Abbas Bhuiya (Taylor & Francis Group, 2017)
Background: Out-of-pocket (OOP) healthcare expenditure is a major obstacle for achieving universal health coverage in low-income countries including Bangladesh. Sixty-three percent of the USD 27 annual per-capita healthcare expenditure in Bangladesh comes from individuals' pockets. Although health insurance is a financial tool for reducing OOP, use of such tools in Bangladesh has been limited to some small-scale voluntary micro health insurance (MHI) schemes run by non-governmental organizations (NGO). The MHI, however, can orient people on health insurance concept and provide learning for product development, implementation, barriers to enrolment, membership renewal, and other operational challenges and solutions. Keeping this in mind, icddr,b in 2012 initiated a pilot MHI, Amader Shasthya, in Chakaria, Bangladesh. This paper explores the determinants of membership renewal in this scheme, which is a perpetual challenge for MHI. Objective: Identify socioeconomic and programmatic determinants and their effects on membership renewal in a voluntary MHI scheme. Methods: Data came from the online management information system of the scheme and Health and Demographic Surveillance System of Chakaria, covering the period February 2012-May 2015. Association between renewal and independent variables was examined using cross-tabular and logistic regression analyses. Results: Nearly 20% of households in the catchment area ever enroled in the scheme, and 38% renewed membership over the initial 3 years of operation. Frequency of consultation with healthcare providers, benefits received, proximity of member's residence to health facility, socioeconomic status, educational level, and age of the household head showed significant positive association with renewal of membership. Conclusions: Villagers' enrolment in the scheme indicated that even in poor economic and literacy conditions people can be motivated to enrol in insurance schemes. Degree of service utilization and benefits received can greatly enhance the probability of membership renewal, which can be ensured with good quality of services and ease of access.